Management of RSV Bronchiolitis in Outpatient Setting - Borgmann, Johannes; Sandmann, Lea; Ritter, Simon; Heep, Axel; Köster, Holger; Wetzke, Martin; Lange, Matthias (Klinische Pädiatrie, 2024)
Seasonal respiratory syncytial virus (RSV) lower respiratory infections (RSV-LRI) and bronchiolitis in children remain a high burden to medical facilities. Studies evaluating the practical approach in outpatient settings are scarce. We conducted a survey to provide an insight into management in pediatric offices in Germany. Invitations for participation in an online survey were sent to 623 providers of pediatric primary care via email. Recipients were randomly chosen from national databanks based on zip codes. The response rate was 16,2%, n=92 (14,7%) questionnaires were fully answered and analyzed. 93,5% (n=86) are board certified pediatricians. In outpatient setting, every second patient with suspected or confirmed RSV-LRI is presented three times or more. 40,7% of our participants refer less than 10% of all patients to hospital, 83,7% refer less than one third (<30%). 33,7% of all participants never perform virological testing in suspected cases of RSV-LRI. More than 50% of all participants prescribe bronchodilators, hypertonic saline inhalation is prescribed by 17,4%. Antibiotics are prescribed in less than 10% of all cases of RSV-LRI. About 3/4 ask for a clearer, more conclusive guideline regarding prophylaxis. The diagnostic approach varies significantly. Although not recommended in international guidelines, bronchodilators are still frequently used. Considering emerging options for passive immunization, broader inclusion criteria into immunization regimes are requested by the participants. More conclusive guidelines and recommendations could further improve the management of outpatient RSV-LRI in children.
Keywords: outpatient; burden; bronchiolitis; infant; children; RSV